Optimization of enzyme‐assisted extraction of albedo extract obtained from watermelon rind (Citrullus lanatus) and its use in the enrichment of nutrients and bioactive compounds in watermelon juices. Issue 10 (19th September 2022) - dos Santos, Gielen Delfino; da Silva Haas, Isabel Cristina; Arriola, Nathalia Darminia Aceval; Vitali, Luciano; Fritzen‐Freire, Carlise Beddin; de Oliveira Petkowicz, Carmen Lucia; Amante, Edna Regina; Prudêncio, Elane Schwinden; Amboni, Renata D. M. C.
Abstract: Background: Albedo residue represents approximately 54% of the total solid residue generated during watermelon juice production, this material is an excellent source of bioactive compounds and polysaccharides. This study aimed at optimizing the enzyme‐assisted extraction (EAE) to obtain a higher yield of albedo extract using response surface methodology (RSM), having in view the enrichment of watermelon juice with this material. Results: The complete three‐level factorial design allowed the optimization of enzyme concentration, extraction time and temperature, leading to an optimal extraction of albedo extract at an enzyme concentration of 1.5 ml/Kg (w/w), extraction time of 45 min and temperature of 50°C. The watermelon juice enriched with 10% of albedo extract (WJ10) showed the highest polyphenolic potential and antioxidant capacity. The 13C NMR spectra confirmed the presence of homogalacturonans, xylogalacturonans and rhamnogalacturonans in the albedo extract. The watermelon juice enriched with 30% albedo extract (WJ30) obtained an increase of 47% and 216% in the content of galactose and uronic acids. HPLC‐RID analysis revealed that the addition of albedo extract in watermelon juice decreased the contents of sucrose, glucose and fructose. The multivariate chemometric analysis revealed the grouping of samples according to the bioactive composition and monosaccharide profile. Conclusion: There is a global demand for reducing organic residues in food industries, that way, the elaboration of products from residues obtained from food processing, rich in polyphenols and polysaccharides, such as albedo extract, represents a promising opportunity to develop innovative products and ingredients with high added value.